A case study of large‐amplitude ULF waves in the Martian foreshock. Issue 1 (20th February 2020) - Shan, LiCan; Ge, YaSong; Du, AiMin
Abstract : Foreshock ultralow frequency (ULF) waves constitute a significant physical phenomenon in the plasma environment of terrestrial planets. The occurrence of these waves, associated with backstreaming particles reflected and accelerated at the bow shock, implies specific conditions and properties of the shock and its foreshock. Using magnetic field and ion measurements from MAVEN, we report a clear event of ULF waves in the Martian foreshock. The interplanetary magnetic field connected to the Martian bow shock, forming a shock angle of 51°. Indicating that this was a fast mode wave is the fact that ion density varied in phase with perturbations of the wave field. The peak frequency of the waves was about 0.040 Hz in the spacecraft frame, much lower than the local proton gyrofrequency ( 0.088 Hz). The ULF waves had a propagation angle approximately 34° from ambient magnetic field and were accompanied by the whistler mode. The ULF waves displayed left‐hand elliptical polarization with respect to the interplanetary magnetic field in the spacecraft frame. All these properties fit very well with foreshock waves excited by interactions between solar wind and backstreaming ions through right‐hand beam instability.